19th Annual U.C. Berkeley Heavy at Claremont Hotel-Berkeley - Watkins, Howard::::::::: (1987)
Joe Barkett, Heidi Pieczonka Garofalo, Frank Gumpert, Christine Watkins, Janie Gumpert holding Buffoon of the Party trophy and plaque and David Morse